Second‐Order Nonlinear Optical Switch of a New Hydrogen‐Bonded Supramolecular Crystal with a High Laser‐Induced Damage Threshold. Issue 12 (22nd September 2014) - Sun, Zhihua; Li, Shenhui; Zhang, Shuquan; Deng, Feng; Hong, Maochun; Luo, Junhua
<x xml:space="preserve">Abstract</x> Organic nonlinear optical (NLO) materials are anticipated as the competitive successors to inorganic compounds in the highly controllable photonic devices. Here, a new supramolecular crystal, bis(imidazolium hydrochlorate) dihydrate 18‐crown‐6 (1), behaves as a potential modulator of quadratic NLO responses. It is found that (1) possesses a superior NLO switching‐contrast of up to ∼12, a remarkable switching reversibility, and a quite high laser‐induced damage threshold (up to ∼8.9 GW/cm2), which may guarantee its device application. In addition, mechanism studies reveal that both the freezing of thermally activated molecular vibrations and atomic displacements are greatly contributive to its NLO switching. Such an exceptional coupling in (1) is distinguishing from the prevenient order–disorder transition and much superior to the chemical changes of other NLO switches. It is believed that the findings provide a concrete example of a solid‐state NLO switch and will urge further development of these desirable devices, as well as to establish new design strategies.